2012
DOI: 10.5693/djo.02.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography changes in macular CMV retinitis

Abstract: Cytomegalovirus (CMV) retinitis characteristically causes peripheral retinitis with associated vasculitis. It rarely begins in the macula or causes macular necrosis exclusively. We report a case of unilateral macular CMV retinitis in a 65-year-old immunosuppressed patient and document changes in the macula during treatment through optical coherence tomography (OCT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The results showed that the retinal atrophy caused by CMV retinitis gradually progressed, even after 2 years, and the cone photoreceptor cells were injured during the course of the disease. Our results agree with the findings of Sun et al, 5 who described the OCT changes related to CMV retinitis in the macula as a lesion involving the deeper retinal layer including the inner and outer segment junction of the photoreceptors. Because the progression of the retinal atrophy near the fovea can be directly linked to the non-reversible visual disturbance, early identification and management of the retinitis is essential.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the retinal atrophy caused by CMV retinitis gradually progressed, even after 2 years, and the cone photoreceptor cells were injured during the course of the disease. Our results agree with the findings of Sun et al, 5 who described the OCT changes related to CMV retinitis in the macula as a lesion involving the deeper retinal layer including the inner and outer segment junction of the photoreceptors. Because the progression of the retinal atrophy near the fovea can be directly linked to the non-reversible visual disturbance, early identification and management of the retinitis is essential.…”
supporting
confidence: 93%
“…One of the reasons why we were able to acquire such high-quality images is because the CMV retinitis occurred at the posterior pole, and although CMV retinitis often appears at the posterior pole and as peripheral retinitis the macula is rarely affected in CMV retinitis. 5 Another reason for the high-quality images might be the low inflammatory reaction in both the anterior and posterior chambers, which can cause media opacity. The low inflammatory reaction might underlie the immunosuppression induced by HIV infection.…”
mentioning
confidence: 99%
“…Consequently, intravitreal drug delivery modalities incorporating ganciclovir or foscarnet injections have emerged as alternatives, in some cases as first line if systemic infection has been ruled out (Langner-Wegscheider et al 2010;Mota et al 2011;Singh et al 2012). Intravitreal ganciclovir and foscarnet are also indicated when patients are intolerant or unresponsive to systemic therapy, and they offer introduction of a higher concentration of the drug directly to the target organ the retina (Sun et al 2012).…”
Section: Treatment and Outcomementioning
confidence: 99%
“…The reason for the analysis was that the CMVR patients were at the early stage of CMVR when they took the OCT examination, and the ocular fundus mainly manifested in the exudation of yellowish-white particles, accompanied by retinal hemorrhage. This clinical manifestation was deemed to be retinal necrosis and different degrees of edema histologically, and significant damage [14] to the retinal structure was the most serious [15] in the active retinitis area, thereby leading to increased retinal thickness of the affected eye in the CMVR examination results. The study conducted by Invernizzi et al revealed that patients with active CMVR have 100% hemorrhage and retinal swelling.…”
Section: Discussionmentioning
confidence: 99%